Self-Efficacy dan Motivasi Berprestasi pada Siswa Kelas XI di Madrasah Aliyah Negeri Model 1 Plus Keterampilan Manado - Nento, Shinta; Manoppo, Indah Nur’aini Aprilla; Anggrainy, Nur Evira (Institut Agama Islam Negeri Parepare, 2025)
Looking at the school environment, a student's response to inadequate learning patterns can affect the level of self-confidence and learning outcomes. Students' self-confidence in class in terms of adaptation, cognitive ability, and intelligence are examples of their self-confidence. In this way, students will realize the extent of their abilities, to try to achieve what they want even though they will face challenges in the process. The aim of this research is to determine whether there is a relationship between self-efficacy and achievement motivation in class XI high school students. The research subjects were class XI science students at Madrasah Aliyah Negeri 1 Plus Skills Manado, with a population of 268 students. The method used in the research is quantitative with data collection using a self-efficacy and achievement motivation scale prepared by researchers based on the theory of Albert Bandura and McClelland. The analysis used in the research is Pearson correlation analysis. The results of the correlation analysis show that there is a significant relationship between self-efficacy and achievement motivation in class XI MAN 1 Plus Skills Manado students. The correlation coefficient rxy 783 with a significance level of 0.001 <0.05 with research results that there is a strong significant relationship between the two variables self-efficacy and achievement motivation